MANIFESTASI SIKAP ANTIKORUPTIF DALAM PERILAKU BELAJAR PADA MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS NEGERI SURABAYA - Lathif, Muhammad Rifqi; Jatiningsih, Oksiana (Universitas Negeri Surabaya (Unesa), 2025)
This study aims to examine the manifestation of anti-corruption attitudes in the learning behavior of students of the Faculty of Social and Political Sciences (Fisipol) Surabaya State University (Unesa), using quantitative descriptive methods and the Gordon William Allport Attitude Component Theory approach, this study focuses on four main attitudes, namely honest, brave, caring, and responsible. The results of the study indicate that students' understanding of anti-corruption values ​​is still low, with 99.1% of respondents having poor understanding and only 0.3% having sufficient understanding. From the affective variable, as many as 73.5% of students showed a positive attitude towards anti-corruption values ​​in learning behavior. However, from the conative variable, only 25.4% of students actually apply these values ​​in their academic behavior with the formulation of the problem how do Fisipol students understand anti-corruption attitudes, anti-corruption attitudes in Fisipol students in their learning behavior, the manifestation of anti-corruption attitudes of Fisipol Unesa students in their learning behavior, this study also found that there are gender differences in the tendency of corrupt behavior, where 88.2% of male students are indicated to have committed corrupt acts in learning, such as cheating and plagiarism, while only 29.4% of female students do the same. This finding indicates that the stereotype factor that develops in society, men are taught to be brave so that it can make men more reckless to commit corrupt behavior. This causes inconsistency between low cognitive, on the other hand affective attention to the rejection of corruption and high anti-corruption actions but not accompanied by low manifestations of anti-corruption actions. This is influenced by several factors including greed, opportunity and need. Keywords : Anti-corruption attitude, Learning Behavior, Fisipol Students